A REESCRITA NA ESCOLA MEDIADA PELA CORREÇÃO TEXTUAL INTERATIVA: uma proposta para o desenvolvimento das capacidades de linguagem - FLORÊNCIO, Deymika de Carvalho (2021)
This research presents a didactic proposal of textual rewriting, with the teaching of the opinion article genre, mediated by textual-interactive correction, through a list of findings/control and didactic sequence, for high school students of the public school "Centro de Ensino Elisa Monteiro”, from the city of Bacabal-MA. The questions that lead this work were: what language skills do the high school students from “Centro de Ensino Elisa Monteiro”, residents in the rural area of Bacabal-MA, have regarding the gender of an opinion piece? And, in what metering will our proposal of textual rewriting, mediated by the textual-interactive correction, contribute to the textual production of two students? In order to respond them, we aimed to analyze the students' writing and rewriting process based on the analysis of language capacities (action capacities, discursive capacities and linguistic-discursive capacities) in their textual productions. Therefore, we based it mainly on the perspective of textual-interactive correction by Ruiz (2018) and on the theoretical-methodological construct of Socio-discursive Interactionism (ISD), with the study of Bronckart (2007), who proposes a model of textual architecture constituted by language skills, with the studies of Dolz, Noverraz and Schneuwly (2011), which bring the perspective of the didactic sequence and with the contributions of Gonçalves (2009b), on the list of findings/control. We adopted “action research” as a type of research. In this work, we analyzed the first and last version of the texts produced by two students participating in the research, which were built around the theme "The renewal of the quota policy for access to universities and federal institutes", composing our corpus with four productions textual. As a result, from the analysis of the first productions, we noticed that the students did not have a mastery regarding the structural and functional characteristics of the opinion article genre. However, from the comparison between the first and last versions of the texts, we found that there was an evolution in their writing, a development and improvement of action capacities, discursive capacities and linguistic-discursive capacities. In this way, we verified that our proposal contributed to the improvement of productions, at micro and macro textual levels. Furthermore, it helped to make students aware that writing is a process and that revision and rewriting are integral to this process.